(untitled) (Journal of Industrial and Mechanical Engineering, 2021)
The levels of participation of women in the areas of Science, Technology, Engineering, and Mathematics in the Latin American region represent and respond to a structural problem. In particular, in the development of engineering history, the women’s role is strictly related to the unequal gender structure in the past and present societies, whose evidence and magnitude can be explained through existing gender gaps. In this context, it is essential to admit the responsibility that higher education institutions of related careers have to problematize gender gaps in their training and professional performance spaces to transform the current situation. In the present research, we applied natural language processing and text mining techniques to first-person essays of diverse professional women in the field of Engineering. The main aim is to know the foremost representations produced and published in the Books "Matilda and women in Engineering in Latin America" during 2019 and 2021.